2015
DOI: 10.1111/spol.12177
|View full text |Cite
|
Sign up to set email alerts
|

A New Kid in Town? Active Inclusion Elements in European Minimum Income Schemes

Abstract: This article assesses the current variation in activation strategies directed towards able-bodied persons of working age relying on a minimum income guarantee in 19 EU member states. First, we argue that the active inclusion notion developed by the European Commission in its Recommendation on the active inclusion of persons excluded from the labour market provides a useful tool to categorize current activation strategies towards minimum income protection (MIP) recipients. Consequently, we assess the empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 30 publications
0
34
0
3
Order By: Relevance
“…To address this, I follow Marchal and Van Mechelen (2015) in using sensitivity analyses to measure the impact of a selection of alternative indicators and cut-off points on welfare states' (non-)membership to each set. There is of course an infinite number of potential variations in indicators and cut-off points which could be tested.…”
Section: Method: Fuzzy-set Ideal Type Analysismentioning
confidence: 99%
“…To address this, I follow Marchal and Van Mechelen (2015) in using sensitivity analyses to measure the impact of a selection of alternative indicators and cut-off points on welfare states' (non-)membership to each set. There is of course an infinite number of potential variations in indicators and cut-off points which could be tested.…”
Section: Method: Fuzzy-set Ideal Type Analysismentioning
confidence: 99%
“…capacity, resources), stigmatization, lack of information and digitalization (see Frazer and Marlier 2016). Studies have shown that, despite the large variation across EU member states, there is a lot of room for improvement in the access to quality services for low income groups (Marchal and Van Mechelen 2017;Frazer and Marlier 2016;Eurofound 2017).…”
Section: When Is a Minimum Income Adequate?mentioning
confidence: 99%
“…Some authors (e.g. Marchal and Van Mechelen 2017;Immervoll 2012) have partly included the latter by looking at access to active labour market support, health or childcare services, but these attempts generally lack an empirical and theoretical underpinning of all the expenses households need to make in order to live a life in dignity. The paper shows that Reference Budgets (RBs) offer such an operationalization of an acceptable living standard by defining what people need at the minimum in order to participate adequately in society, taking into account the institutional, cultural and social context (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The developments in the Finnish social assistance system resemble the general patterns that have occurred elsewhere in Europe. In general, there has been a trend within minimum benefit schemes towards activation policies (Immervoll, 2009;Marchal & van Mechelen, 2015). In addition, there has been a shift towards self-help, including stricter conditionality, improved services, and collaboration with employment centers (Leibetseder, Gubrium, Dierckx, Fluder, Hauri, & Raeymaeckers, 2017).…”
Section: The Role Of Social Assistance For Young Adults In Finlandmentioning
confidence: 99%